2021
DOI: 10.1007/s10072-021-05253-8
|View full text |Cite
|
Sign up to set email alerts
|

Fear of relapse, social support, and psychological well-being (depression, anxiety, and stress level) of patients with multiple sclerosis (MS) during the COVID-19 pandemic stage

Abstract: Background Psychological well-being assessment during the COVID-19 pandemic is essential for patients with multiple sclerosis (MS). The goal of this study is to evaluate fear of relapse, social support, and psychological well-being (depression, anxiety, and stress level) of Iranian patients with MS during the COVID-19 pandemic stage. Methods One hundred and sixty-five patients were enrolled. We asked all cases to fill valid and reliable Persian version of depression, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Most of the studies (n=14) used online surveys for data collection. Four studies excluded participants with comorbid psychiatric conditions ( Altunan et al, 2021 ; Chiaravalloti et al, 2021 ; Demir et al, 2020 ; Stojanov et al, 2020 ), nine studies did not mention pre-existing psychiatric comorbidities prior to the onset of the COVID-19 outbreak ( Alschuler et al, 2021 ; Andreu-Caravaca et al, 2021 ; Bonavita et al, 2020 ; Broche-Perez et al, 2021 ; Capuano et al, 2021 ; Dilek et al, 2021 ; Naser Moghadasi, 2020 ; Shaygannejad et al, 2021b ; Talaat et al, 2020 ), and the remaining six articles reported baseline psychiatric comorbidity status ( Costabile et al, 2020 ; Garjani et al, 2021 ; Motolese et al, 2020 ; Ramezani et al, 2021 ; Shaygannejad et al, 2021a ; Zanghi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies (n=14) used online surveys for data collection. Four studies excluded participants with comorbid psychiatric conditions ( Altunan et al, 2021 ; Chiaravalloti et al, 2021 ; Demir et al, 2020 ; Stojanov et al, 2020 ), nine studies did not mention pre-existing psychiatric comorbidities prior to the onset of the COVID-19 outbreak ( Alschuler et al, 2021 ; Andreu-Caravaca et al, 2021 ; Bonavita et al, 2020 ; Broche-Perez et al, 2021 ; Capuano et al, 2021 ; Dilek et al, 2021 ; Naser Moghadasi, 2020 ; Shaygannejad et al, 2021b ; Talaat et al, 2020 ), and the remaining six articles reported baseline psychiatric comorbidity status ( Costabile et al, 2020 ; Garjani et al, 2021 ; Motolese et al, 2020 ; Ramezani et al, 2021 ; Shaygannejad et al, 2021a ; Zanghi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Anxiety was the primary outcome variable in 16 (84.2%) of the included studies ( Alschuler et al, 2021 ; Andreu-Caravaca et al, 2021 ; Broche-Perez et al, 2021 ; Capuano et al, 2021 ; Chiaravalloti et al, 2021 ; Demir et al, 2020 ; Dilek et al, 2021 ; Garjani et al, 2021 ; Motolese et al, 2020 ; Naser Moghadasi, 2020 ; Ramezani et al, 2021 ; Shaygannejad et al, 2021a ; Shaygannejad et al, 2021b ; Stojanov et al, 2020 ; Talaat et al, 2020 ; Zanghi et al, 2020 ). Measurement scales used to assess anxiety included the Depression Anxiety Stress Scales-21 (DASS-21) (n=4) ( Shaygannejad et al, 2021a ; Shaygannejad et al, 2021b ; Talaat et al, 2020 ; Zanghi et al, 2020 ); the State-Trait Anxiety Inventory (STAI) (n=3)( Andreu-Caravaca et al, 2021 ; Capuano et al, 2021 ; Dilek et al, 2021 ); the Hospital Anxiety and Depression Scale (HADS) (n=3) ( Chiaravalloti et al, 2021 ; Garjani et al, 2021 ; Ramezani et al, 2021 ); the Generalized Anxiety Disorder-7(GAD-7) (n=3)( Broche-Perez et al, 2021 ; Garjani et al, 2021 ; Motolese et al, 2020 ); the Beck Anxiety Inventory (BAI) (n=2) ( Demir et al, 2020 ; Naser Moghadasi, 2020 ); the Hamilton scales for anxiety (HAM-A) (n=1)( Stojanov et al, 2020 ); and the PROMIS Short Form v1.0 – Anxiety 6a (n=1)( Alschuler et al, 2021 ). One study used two scales to assess anxiety in their participants ( Garjani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations